Experimental Performance of a Two-Stage Cross-Coupled MOS-Based Circuit in the Solar and Piezoelectric Energy Harvesting - BANERJEE, JOYDEEP (Ingeniería, 2025)
Context: Energy harvesting has positioned itself an emerging area of research due to recent developments in low-power electronics, the Internet of Things, and artificial intelligence. Various diode-based circuits and alternatives have been proposed in the literature, but the application of CMOS cross-coupled circuits, specifically in piezoelectric energy-harvesting systems, has not been properly explored. Method: An experimental study was conducted in order to assess the performance of a two-stage cross-couple MOS-based voltage multiplier in piezoelectric and solar energy harvesting. A piezoelectric disc was used to evaluate the output. The piezoelectric output was obtained by applying a small pressure to the input, and a 6 V panel was employed in the solar energy setup. Results: The proposed circuit provides a 1.91-fold voltage gain in the piezoelectric energy harvester. Conclusions: The two-stage MOS-based cross-coupled voltage multiplier circuit performs better than the diode-based alternative in the piezoelectric energy harvester. These experimental results show encouraging prospects for green energy, low-power electronics, and Internet of Things applications, among others.